1995
DOI: 10.1111/j.1095-8649.1995.tb06023.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted motion analysis of sperm from the common carp

Abstract: Computer-assisted semen analysis (CASA) technology was applied to the measurement of sperm motility parameters in the common carp Cyprinus ctrrpio. Activated sperm were videotaped at 200 frames s ' and analysed with the CellTrak/S CASA research system. The percentage of motile cells and both sperm head curvilinear velocity and straight-line velocity were measured following exposure of carp sperm to three predilution conditions and activation in media of differing ionic strengths and osmotic pressures. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
3
35
1
Order By: Relevance
“…Also Campos-Mendoza et al (2004) noted that variation in day length during spawning period affected the sperm volume in males. Seminal plasma not only maintains immobility of spermatozoa but also protects them (Cosson et al, 1997); this is the case, for example, in the common carp Cyprinus carpio (Toth et al, 1995) and in the rainbow trout Oncorhynchus mykiss (Billard, 1986). The ionic composition may change during the spawning season .…”
Section: Discussionmentioning
confidence: 99%
“…Also Campos-Mendoza et al (2004) noted that variation in day length during spawning period affected the sperm volume in males. Seminal plasma not only maintains immobility of spermatozoa but also protects them (Cosson et al, 1997); this is the case, for example, in the common carp Cyprinus carpio (Toth et al, 1995) and in the rainbow trout Oncorhynchus mykiss (Billard, 1986). The ionic composition may change during the spawning season .…”
Section: Discussionmentioning
confidence: 99%
“…In common carp males, the application of Ovopel (1 pellet kg -1 ) enables semen to be obtained even after 72 h, but the semen volume and sperm number at this time are significantly lower than values noted after 24 h (Cejko et al 2011). This indicates that in common carp males, latency time is rather short and semen should be taken no longer than 24 h after hormonal treatment (Toth et al 1995;Christ et al 1996;Cejko et al 2011). The presented study indicated that in comparison to the first Ovopel treatment, the repeated stimulation of males with this preparation resulted in decreased semen volume and total number of sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Once diluted, milt was held on ice in a cooler between preparation of slides. Other investigators of sperm motility have reported sample preparation periods to post-activation of 0 sec (dilution prepared on microscope's stage) (Vladic and Jaervi, 1997) and 15 sec (Toth et al, 1995). It is important to maintain consistency in post-activation times among samples.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Approximately 100 spermatozoa should be tracked per sample and it is a time-consuming process. Computerassisted sperm analysis (CASA) to assess the effects of pollutants on fish sperm has been successfully employed to estimate sperm swimming speed (Toth et al, 1995). This device automatically assesses speeds of high numbers of sperm and provides a digital data output (Kime et al, 1996).…”
Section: Sperm Motilitymentioning
confidence: 99%